Some factors influencing the legislative processes in Spain: supranational obligations and pressure groups - García-Magna, Débora (My University, 2017)
In Spain, as in many other countries, the legislative initiative is influenced by several factors, beyond the actual need for criminal protection. Especially some areas are prone to populist dynamics and likely to incorporate the discourses of pressure groups. On the other hand, Spain has assumed some supranational commitments that determine legislative processes, where two situations can be distinguished: obligations that must be transposed into national legislation, and those that serve as a pretext for the national legislator to carry out broader reforms than the ones required by international standards. On the first issue, this research will show that some Spanish criminal policies are based on rather emotional and electoral, than rational arguments. These decisions often focus on the short-term view, thus justifying punitive measures or inaction in certain areas. Regarding the second issue, an exploration of the 30 reforms of the current Spanish Penal Code has been carried out, in order to identify and analyse references to international instruments (conventions, jurisprudence of international courts, European or supranational legislation, and the European Court of Human Rights).
Keywords: Derecho penal; Criminal law; Law and order model; Pressure groups; Legislative processes; Supranational obligations